Praktik Pemasaran Pada Perusahaan Farmasi Multinasional Di Indonesia Dalam Bingkai Virtue Ethics Mendorong Terciptanya Keunggulan Kompetitif - Wijayanti, Sari; Kusuma, Triana Hasty; Poluan, Stevi Jimry; Nisa, Rizka Fatkhin; Putra, Yanuar Surya (Magisma: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The marketing strategies employed by multinational pharmaceutical corporations in Indonesia are closely related to the ethical dimensions and their capacity to enhance competitiveness within the marketplace. The objective of this research is to formulate a mini-theory concerning the development of propositions derived from emerging theoretical frameworks. The methodology adopted in this investigation was a qualitative approach, utilizing secondary data sourced from way back machine, corporate search engines and online resources. The focal subjects of this inquiry comprise three multinational pharmaceutical entities operating in Indonesia, specifically Eisai Indonesia and Roche Indonesia. The findings of this study culminate in the assertion that marketing practices at multinational pharmaceutical firms, bolstered by ethical considerations, significantly impact competitive advantage.